Perlindungan Buruh Atas Pemutusan Hubungan Kerja (PHK) Karena Perusahaan Dinyatakan Pailit - Wahyudi, Ihsan (University of Jember, 2015)
Workers are workers who have done work, either working for thenselves or working in a work relationship or under the orders of employer and for their services in working laborers get wages or other forms of compensation. Workers are an inseparable part of national development based on the 1945 Constitution of the Republic of Indonesia. Labor has an important role in the position as national development actors and targets. That is why there must be labor rights stipulated in applicable Indonesian regulations which include protection of labor rights. Some labor rights receive compensation and proper treatment in carrying out work in the company or government agencies. Fulfillment of labor rights that are not fulfilled by these companies often creates employment cases in Indonesia. Especially what happened when the company experienced financial problems, namely bankruptcy by the Commercial Court, which caused the company to face difficulties in fulfilling labor rights and severing labor relations because the company had experienced pailit. Keywords : Worker, Work Termination, Pailit